Improving learning of typical and atypical populations using cognitive training and transcranial electrical stimulation - Looi, C (2018)
The ability to learn is critical, whether to survive or to thrive. Research suggests that cognitive training and transcranial electrical stimulation (tES) could modulate neuroplasticity and improve learning and cognition. However, the key challenge of both fields lies in their translational research. In particular, the translational potential of both methods is restricted by the use of training tasks that lacked ecological validity. Using more realistic training tasks, the current thesis explored the effects of cognitive training alone on healthy children, and the combination of cognitive training and tES, compared to training alone in typical (healthy adults and elderly) and atypical populations (children with learning disabilities). Findings demonstrate that cognitive training and tES could improve learning and cognition of typical and atypical populations across different age groups, as modelled using the numerical domain. Specifically, the current thesis highlights the role of content in training outcomes, and the synergistic effects of combining tES and cognitive training on learning, compared to training alone. Furthermore, findings suggest that the combined approach of tES and cognitive training could offer long-term positive outcomes that benefit those with lower baseline cognitive abilities, effects that are meaningful to the real-world, and the possibility of mitigating cognitive trade-offs from training alone. Further optimisation of training design and tES parameters, with the consideration of individual differences and underlying mechanisms are warranted to improve the translational potential of these methods. Given the ethical concerns raised by the use of tES for cognitive enhancement, both scientific research and bioethical discussions are required to guide future directions on improving learning and cognition of the individual and for all.